Graphic geography: drawing territories at the Po Delta (Italy). (January 2021) - Bertoncin, Marina; Pase, Andrea; Peterle, Giada; Quatrida, Daria
Geography and the graphic image have a long, intertwined history of exchange. In recent scholarship, the graphic image plays an important role in geography's creative (re)turn and geographers are experimenting with new visual languages and creative practices to carry out research and communicate with wider audiences. This paper explores geography as a 'graphic' discipline that represents and produces spatial knowledge by experimenting with scribing, a verbo-visual technique. In the first part of the article, we propose an auto-ethnographic account of a residential seminar with students in Local and Sustainable Territorial Development, held in 2017 at the Po Delta (Italy), where we experimented with scribing as a tool for geographical fieldwork and spatial storytelling, understanding it as a practice for seeing beyond representing territories. The second more theoretical part of the paper presents scribing as a means to respond to the increasing need for more creative visualisation tools in qualitative research and highlights the performative potential of scribing as a practice/product for thinking about space. The graphic product of scribing results from an intersubjective dialogue and is used to develop spatial analyses and disseminate geographical research beyond academic boundaries, engaging non-expert audiences and local communities.